BOOK REVIEW OF SIMONE ELKELES’ PERFECT CHEMISTRY - Pramuditha, Nararyani (LANTERN (Journal on English Language, Culture and Literature), 2016)
As teenagers begin to assert their independence and find their own indentity, they are facing behavioral, emotional, or learning issues in their lives. Teenagers go through some hard times and it can be difficult at times. Each of them has a life story. Teenagers’ life is surrounded by some issues, such as bad grades, reputation, drugs, popularity and family problem. It is confusing and very stressful. Teenagers’ hardship makes them more critical and have a desire of having a good life in the future. On the journey to achieve their goals, teenagers definitely get various kinds of obstacles which could come from the loved one, for example, from their parents. Sometimes, parents want their children to be what they want instead of what their children actually want. Hence, these teenagers can not fully be themselves and be what they actually want.